2009
DOI: 10.2527/jas.2007-0177
|View full text |Cite
|
Sign up to set email alerts
|

Duration of feeding linseed diet influences expression of inflammation-related genes and growth performance of growing-finishing barrows1

Abstract: The aim of the study was to investigate the effects of dietary linseed (rich in n-3 PUFA) on expression of inflammation-related genes and on growth performance of growing-finishing barrows. Two isoenergetic and isonitrogenous diets were formulated, one as the basal diet and the other containing 10% linseed. Twenty-four Landrace x Yorkshire barrows weighing 35 +/- 3.7 kg were randomly assigned to 1 of 4 treatment groups, with 6 pigs per group. During the entire experimental period of 90 d, these 4 groups of pig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 27 publications
2
37
2
Order By: Relevance
“…In addition, average daily feed intake was also not affected by the treatment [29]. Noteworthily, the significant difference (P \ 0.05) in IMF content compared with group T1 (0 days) was observed in group T3 (60 days) and T4 (90 days), but not in group T2 (30 days), suggesting that a certain length of duration of feeding linseed diet has to be reached in order to influence the IMF content.…”
Section: Discussionmentioning
confidence: 58%
“…In addition, average daily feed intake was also not affected by the treatment [29]. Noteworthily, the significant difference (P \ 0.05) in IMF content compared with group T1 (0 days) was observed in group T3 (60 days) and T4 (90 days), but not in group T2 (30 days), suggesting that a certain length of duration of feeding linseed diet has to be reached in order to influence the IMF content.…”
Section: Discussionmentioning
confidence: 58%
“…Dietary ratio of n-6 to n-3 fatty acid P-Value 12:1 9: previous research, dietary n-3 fatty PUFA was found to either enhance or decrease immune responses (Blok et al, 1996;Fritsche et al, 1991;Korver and Klasing, 1997;Sijben et al, 2000Sijben et al, , 2001Zhan et al, 2009). So, it should be noted that the T lymphocyte and the expression of cytokines may behave differently after n-3 PUFA in challenged and unchallenged animals.…”
Section: Items Bmentioning
confidence: 90%
“…anti-inflammatory properties (Zhan et al, 2009) by increasing antibody response (Sijben et al, 2001) and decreasing lymphocyte proliferation . Wang et al (2011) CD4þ percentage and CD4þ : CD8þ ratio were much higher in the 6:1 (n-6:n-3) PUFA ratios group.…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with our findings, Liu et al (2003) demonstrated, in a weaner pig study, that fish oil-derived n-3 fatty acids decreased PGE 2 production and improved ADG and ADFI following LPS-induced immune system stimulation. Moreover, Zhan et al (2009) showed that increased duration of feeding linseed-derived n-3 fatty acids linearly decreased gene expression of inflammatory cytokines such as TNF-α and improved ADG and feed efficiency. Therefore, performance and leanness data suggest that under our experimental condition, n-3 fatty acids mitigated LPS-induced muscle growth in growing-finishing pigs.…”
Section: Discussionmentioning
confidence: 99%